The role of Test Anxiety on Academic Performance of Adolescent Students: Understanding and Managing Test Anxiety in Adolescent Students (Journal of Advances and Scholarly Researches in Allied Education, 2022)
School is a garden where children are its flowers, the kind of education we nurture thoseflowers, that motivates them to make them responsible citizens. Not only motivating thembut alsopersonality and thoughts inspire them to be responsible citizens but the pressure of education ontoday's teenagers is increasing too much.Which makes them academic anxious and in Academic Anxiety the important role is of Test Anxiety andthis is why adolescents are not motivated to prepare well for exams and reduce academic performanceand less anxiety makes adolescent students prepare well for exams are motivated to do and have apositive impact on academic performance.Therefore, knowing the cause and level of test anxiety ofadolescents and suggested tips will help adolescents to advance in academic careers and reduce testanxiety. Motivate and motivate yourself to do better academically next time by learning from negativecauses of test anxiety.